2022
DOI: 10.21053/ceo.2021.02285
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Gasless Transaxillary, Bilateral Axillo-Breast, Unilateral Axillo-Breast With Carbon Dioxide Insufflation, Retroauricular, and Transoral Vestibular Endoscopic Thyroidectomy Approaches at a Single Institution: A Retrospective Analysis and Lessons Learned

Abstract: Objectives. This study aimed to present our experiences with various approaches for endoscopic thyroidectomy (ET) and to offer lessons for choosing an approach.Method. The medical records of 701 patients who underwent ET via different approaches such as transaxillary (TA), bilateral axillo-breast (BABA), unilateral axillo-breast with carbon dioxide insufflation (UABA), retroauricular (RA), or transoral vestibular (TO) between May 2008 and March 2020 were retrospectively reviewed.Results. The mean operative tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…Gas bubbles in the bleeding field during skin flap elevation were noted by Kim et al before the onset of CO 2 embolism 3 . Three cases presented only with mild hypercapnia/EtCO 2 elevation, while one patient developed a loud, coarse precordial murmur 1,8 . Fu et al confirmed the diagnosis of CO 2 embolism in two cases with the use of a precordial Doppler intraoperatively revealing gas formation 7 …”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Gas bubbles in the bleeding field during skin flap elevation were noted by Kim et al before the onset of CO 2 embolism 3 . Three cases presented only with mild hypercapnia/EtCO 2 elevation, while one patient developed a loud, coarse precordial murmur 1,8 . Fu et al confirmed the diagnosis of CO 2 embolism in two cases with the use of a precordial Doppler intraoperatively revealing gas formation 7 …”
Section: Discussionmentioning
confidence: 88%
“…3 Three cases presented only with mild hypercapnia/EtCO 2 elevation, while one patient developed a loud, coarse precordial murmur. 1,8 Fu et al confirmed the diagnosis of CO 2 embolism in two cases with the use of a precordial Doppler intraoperatively revealing gas formation. 7 The initial management of CO 2 embolism includes cessation of CO 2 insufflation, hyperventilation with 100% O 2 , positioning the patient in a steep head-down left lateral decubitus, and increasing positive end-expiratory pressure (PEEP).…”
Section: Case Presentationmentioning
confidence: 94%
See 2 more Smart Citations
“…A transoral endoscopic thyroidectomy transmandibular approach has recently been reported to be effective and safe, avoiding skin numbness in the central mandibular region and reducing the difficulty of establishing a surgical space ( 45 ). In addition, some studies have reported good results with inflation-free TOETVA, such as clear visual fields and no CO2 gas embolism complications ( 18 , 33 , 46 , 47 ). As the technology develops, several studies suggest TOETVA may be a feasible and safe thyroidectomy for children ( 48 ).…”
Section: Discussionmentioning
confidence: 96%